1990
DOI: 10.1111/j.1467-9787.1990.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Defense Spending and State Economic Growth*

Abstract: Little evidence is currently available on the regional growth effects of federal defense spending. In this study, econometric models for state personal income and manufacturing employment between 1976 and 1985 are specified and estimated. Pooled cross-sectional time-series data are used, and the estimation procedure corrects for serial correlation, heteroscedasticity, and contemporaneous cross-sectional correlation. The results indicate that aggregate defense spending has a positive effect on both growth measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Where no specification was clearly preferred, I averaged estimates across all reported specifications. (Two exceptions to this rule are the studies by Helms (1985) and Mehay and Solnick (1990); see notes on these studies for details.) The elasticities used in the calculations summarized in table 2.3 are for the business activity variable that is most closely related to total business activity.…”
Section: Appendix 22 Studies Of Effects Of State and Local Taxes On mentioning
confidence: 99%
“…Where no specification was clearly preferred, I averaged estimates across all reported specifications. (Two exceptions to this rule are the studies by Helms (1985) and Mehay and Solnick (1990); see notes on these studies for details.) The elasticities used in the calculations summarized in table 2.3 are for the business activity variable that is most closely related to total business activity.…”
Section: Appendix 22 Studies Of Effects Of State and Local Taxes On mentioning
confidence: 99%
“…Spending on defense procurement and personnel was responsive to aggregate concentration, attesting to the influence of powerful corporate actors in the private sector. Similarly, in one of the few state-level studies of this kind, Mehay and Solnick (1990) found that aggregate military spending positively affected economic growth, but once disaggregated, only increases in investment-type outlays increased growth.…”
Section: Introductionmentioning
confidence: 95%
“…This variable taps all non-military federal funds flowing into the state and controls for alternative ways in which federal funding might affect economic well-being. Following Mintz and Hicks (1984) and Mehay and Solnick (1990), we disaggregated state-level military spending into two components. Defense contracts (t-1) is the percent of the state's GSP from government contracts through procurement of defense-related materials from companies in those states; while defense personnel (t-1) is the percent of the state's GSP devoted to spending on civilian and military defense personnel (including retirement and veteran's benefits).…”
Section: Independent Variablesmentioning
confidence: 99%
“…However, others have found that reductions in defense spending might hurt the economy (Atesoglu and Mueller, 1990;Thomas et al, 1991;Mehay and Solnick, 1990), and many analysts have found no links between defense spending and economic growth (Kinsella, 1990;Gold and Adams, 1990;Dunne, 1990;Payne and Ross, 1992;Mintz, 1990, 1991;Gerace, 2002). Gerace (2002) sums up prevailing views well, observing that ''the net effect of military expenditures on economic growth is theoretically ambiguous'' (p. 2), and that ''there is no general consensus on whether military spending positively or negatively affects economic growth'' (p. 1).…”
Section: Military Spending and Economic Growthmentioning
confidence: 99%